A RBDO approach for the reliability assessment of composite structures - Carlos Conceição António (2017)
The introduction of reliability assessment methods in safety analysis of composite structures increased the complexity and the efficiency of failure evaluation proposed methodologies. Here, an approach based on surrogate modelling of first ply failure (FPF) to obtain the reliability of the whole composite structure is proposed and analysed for reliability-based design (RBDO). This approach overcomes the expensive costs associated with exhaustive local reliability evaluation. However, it can drive an underestimation of the structural reliability index. The identification of different failure modes and its importance in reliability analysis are outlined and discussed.